Active control of the visual field in the starfish Acanthaster planci. (October 2016) - Beer, S.; Wentzel, C.; Petie, R.; Garm, A.
Abstract: Photoreception in echinoderms has been studied for several years with a focus on the dermal photoreceptors of echinoids. Even though spatial vision has been proposed for this dermal photosystem, by far the most advanced system is found in a number of asteroids where an unpaired tube foot at the tip of each arm carries a proper eye, also known as the optical cushion. The eyes resemble compound eyes, except for the lack of true optics, and they typically have between 50 and 250 ommatidia each. These eyes have been known for two centuries but no visually guided behaviors were known in starfish until recently when it was shown that both Linckia laevigata and Acanthaster planci navigate their coral reef habitat using vision. Here we investigate the visual system of A. planci and find that they have active control of their visual field. The distalmost tube foot holding the eye is situated on a movable knob, which bends to adjust the vertical angle of the visual field. On the leading arms the visual field is directed 33° above the horizon, whereas the eyes on the trailing arms are directed 44° above horizontal on average. When the animal traverses an obstacle the knob bends and counteracts most of the arm bending. Further, we examined a previously described behavior, rhythmic arm elevation, and suggest that it allows the animal to scan the surroundings while preventing photoreceptor adaptation and optimizing image contrast.